Defining crucial factors of cloud gaming services and how gamers value them - Höfer, Maximilian Alfred (2022)
In recent years, the gaming market experienced the addition of a new platform for users to play on. Cloud Gaming Services are rivaling PC hardware and console manufacturers. Big players like Google, Microsoft, NVIDIA, and Amazon entered the market and now compete for market share. This thesis aims to find the most relevant parameters responsible for the success of cloud gaming, and subsequently analyze how gamers value these parameters. Current research about the gaming industry and cloud services in the form of secondary data was used as a foundation to find the most relevant and challenging factors for service providers. In addition, primary data in the form of a consumer survey was collected to analyze the perception of gamers on the topic. The analysis showed that the most important parameters could be grouped into two categories: performance-related and service structure. Hardcore gamers focus more on performance-related issues compared to casual gamers. The amount consumers are willing to spend is not dependent on income but on the service's offerings.